Følsomme lesninger. Affektteori og litteraturundervisning i Fagfornyelsen - Buvik Sivertsen, Kristin (Nordlit, 2022)
This article discusses how a literature didactics based on affects and feelings can contribute to more engaging and active readings of literature, as well as strengthen students’ emotional literacy. Both in the selection of curriculum and in students’ responses, feelings should play a more important role. The selection of text could/should be based on their affective charge, or what kinds of moods, feelings and affects that are in play. Based on Rita Felski’s perspectives in Uses of Literature, this article argues that teaching with emotional recognition as starting point, or encouraging a shock-based literary interaction, is an approach to literature, which not only can be experienced as more relevant to the students, but also fulfill the intentions behind multiple elements in Fagfornyelsen. The article demonstrates how one can teach literature based on affect theory with examples from readings of Monica Isakstuen’s Rase and Yahya Hassan’s Digte.